A kind of steel core aluminum stranded wire and preparation method thereof

By spraying anticorrosive coatings on the surface of the steel core aluminum twisted line, and using boiling sodium hydroxide solution during aluminum line wrapping, to form a anticorrosive layer, solving the problem of corrosion of steel core aluminum twisted lines in actual applications, realized, realized, realized The effect of significantly improved corrosion resistance and extending service life.

CN118299130BActive Publication Date: 2025-01-24河北正人电气有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410673724.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-28
Publication Date
2025-01-24
Estimated Expiration
2044-05-28

AI Technical Summary

Technical Problem

In practical applications, steel core aluminum stranded wires are often corroded by external corrosive media, resulting in a degradation in performance.

Method used

Speed ​​on the surface of the steel core and aluminum twisted thickening of anticorrosive coatings with a thickness of 5.0-8.0µm, soaked in the boiling sodium hydroxide solution during the aluminum thread wrapping, and then sprayed anti-corrosion coating again to form the anticorrosive layer. Anticorrosive coatings contain super -living polymers and modified fillers, which work together to improve the anticorrosive performance of coating.

Benefits of technology

The formed anti-corrosion layer not only has excellent corrosion resistance and weather resistance, but also maintains the mechanical and electrical properties of the steel core aluminum stranded wire, significantly extending the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of steel core aluminum stranded wire, and proposes a steel core aluminum stranded wire and a preparation method thereof, comprising a steel core, an aluminum stranded wire, and an anti-corrosion coating coated on the surface of the steel core and the aluminum stranded wire. The present invention sprays an anti-corrosion coating on the surface of the steel core and the aluminum stranded wire to form an anti-corrosion layer, which not only has excellent corrosion resistance and weather resistance, but also maintains the original mechanical properties and electrical properties of the steel core aluminum stranded wire. The hyperbranched polymer and modified filler added to the anti-corrosion coating work synergistically to improve the anti-corrosion performance of the coating. The hyperbranched polymer also acts as a curing agent and improves the mechanical properties of the coating at the same time. The modified filler is based on MXene nanosheets, and polypyrrole and functional monomers are loaded on its surface and between layers, and the synergistic effect improves the anti-corrosion performance of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of steel core aluminum stranded wire, and in particular to a steel core aluminum stranded wire and a preparation method thereof. Background Art

[0002] Steel-core aluminum stranded wire is composed of a steel core made of galvanized steel wire or galvanized steel wire hinged together, and one or more layers of hinged aluminum stranded wire on the outside. It is widely used in high-voltage transmission lines, urban distribution networks, wind power generation and solar power generation systems, and has the characteristics of lightness, high strength, and high conductivity. When used, steel-core aluminum stranded wire is often corroded by corrosive media such as moisture, chemical gases, dust, and salt substances in the atmosphere. The corrosion is gradually reduced in the order of coastal industrial areas, industrial areas, coastal areas, and rural areas. The corrosion can cause the steel-core aluminum stranded wire to break, break strands, etc., causing power transmission accidents.

[0003] Spraying a layer of anti-corrosion coating on the surface of the steel core and the aluminum strand respectively can effectively prevent the corrosion caused by the external corrosive medium, thereby protecting the internal steel core aluminum strand, allowing it to be used normally in various environments and prolonging the service life of the steel core aluminum strand. Therefore, a coating with excellent corrosion resistance is developed to spray the steel core aluminum strand, which improves the corrosion resistance of the steel core aluminum strand and prolongs its service life. Summary of the invention

[0004] The present invention provides a steel core aluminum stranded wire and a preparation method thereof, which solves the problem in the related art that the steel core aluminum stranded wire is often corroded by external corrosive media in practical applications, resulting in performance degradation.

[0005] The technical solution of the present invention is as follows:

[0006] A method for preparing a steel core aluminum stranded wire comprises the following steps:

[0007] Step S1: After the steel core is degreased, washed, dried, and sandblasted to remove rust, an anti-corrosion coating with a thickness of 5.0-8.0 µm is sprayed on the surface of the steel core, and the steel core is allowed to stand and dry to obtain a pretreated steel core;

[0008] Step S2: Wrap the aluminum wire in two layers on the pretreated steel core, with the inner layer being 12 strands and the outer layer being 14 strands, and then soak it in a 10wt% boiling sodium hydroxide solution for 3-7 minutes, wash it with water, dry it, and sandblast it, and then spray it with an anti-corrosion coating with a thickness of 10-20µm, and then wash it with water and dry it to obtain the steel core aluminum stranded wire.

[0009] The anticorrosive coating is prepared by the following steps:

[0010] Step A1: add trimesic acid, trimethylolpropane triglycidyl ether and tetrabutylammonium bromide into a reactor containing N,N-dimethylformamide, mix well, introduce nitrogen into the system, heat to 90°C for reaction for 4-6h, and after the reaction is completed, rotary evaporate, wash and dry to obtain product 1;

[0011] Step A2: Add product 1, pentaerythritol tetramine and 3,4-dimethoxybenzylamine into a flask containing dichloromethane, stir for 30 minutes, then add N,N-dicyclohexylcarbodiimide, and heat to 170-200° C. under nitrogen, condense and reflux for 5-7 hours. After the reaction is completed, distill to obtain an amino-terminated hyperbranched precursor;

[0012] Step A3: Add the amino-terminated hyperbranched precursor and dichloromethane into a flask, stir evenly, dropwise add a dichloromethane solution of boron tribromide at 0-5°C, stir and react for 6-10 hours, and after the reaction is completed, filter, wash and dry to obtain a hyperbranched polymer;

[0013] Step A4: weigh the raw materials according to mass percentage, add 6%-12% of hyperbranched polymer, 0.3%-0.7% of defoamer, 0.1%-0.5% of dispersant and 10%-15% of modified filler into 71.8%-83.6% of epoxy resin, and stir and mix for 30 minutes to obtain an anti-corrosion coating;

[0014] Specifically, in step A1, the usage ratio of trimesic acid, trimethylolpropane triglycidyl ether, tetrabutylammonium bromide and N,N-dimethylformamide is 0.03-0.09 mol: 0.01 mol: 0.015-0.045 mol: 200 mL;

[0015] Specifically, in step A2, the usage ratio of product 1, pentaerythritol, 3,4-dimethoxybenzylamine, dichloromethane and N,N-dicyclohexylcarbodiimide is 0.01 mol: 0.08-0.12 mol: 0.03-0.05 mol: 200 mL: 0.08-0.2 g;

[0016] Specifically, in step A3, the usage ratio of the terminal amino hyperbranched precursor, dichloromethane and dichloromethane solution of boron tribromide is 2-3 g:200 mL:4-8 mL, and the mass concentration of the dichloromethane solution of boron tribromide is 0.15-0.35 g / mL.

[0017] The modified filler is prepared by the following steps:

[0018] Step B1: add histidine to a mixture of chloroform and acetonitrile and stir evenly, then add trimethylsilyl chloride, reflux for 2 hours, then cool to 0°C, then add triethylamine and trityl chloride dissolved in chloroform into the reactor, continue stirring and reacting for 1 hour, then add methanol and mix evenly, concentrate, extract and dry to obtain intermediate 1;

[0019] Step B2: Add the intermediate product 1 and (4-(aminomethyl)phenyl)phosphonic acid into a flask containing dichloromethane, stir and mix evenly, then add N,N'-dicyclohexylcarbodiimide, and heat to 170-200°C under nitrogen, condense and reflux for 3-5h. After the reaction is completed, distill, and then add the product into 40mL acetic acid solution and reflux for 10min to obtain a functional monomer;

[0020] Step B3: 1g of MXene nanosheets etched with HCl-LiF and 0.5-2g of 3-aminopropyltriethoxysilane were dispersed in a mixture of 10mL of deionized water and 50mL of ethanol, stirred for 5-10h, centrifuged, washed, and redispersed in 50mL of deionized water, recorded as solution A. Pyrrole was dispersed in an ethanol aqueous solution, stirred for 30min, and functional monomers were added and continued to stir for 1h. Subsequently, the mixed solution was added to solution A, and 0.1mol / L ammonium persulfate solution was slowly added dropwise at 2-5°C. The reaction was continued with stirring for 10-12h. After the reaction was completed, the solution was centrifuged, washed, and dried to obtain a modified filler.

[0021] Specifically, in step B1, the usage ratio of histidine, chloroform, acetonitrile, trimethylsilyl chloride, chloroform, triethylamine, trityl chloride and methanol is 0.01 mol: 15-20 mL: 3-4 mL: 0.01 mol: 10 mL: 0.02-0.03 mol: 0.01-0.025 mol: 2 mL;

[0022] Specifically, in step B2, the usage ratio of the intermediate product 1, (4-(aminomethyl)phenyl)phosphonic acid, dichloromethane and N,N'-dicyclohexylcarbodiimide is 0.01-0.02 mol: 0.01-0.02 mol: 100 mL: 0.05-0.15 g, and the mass ratio of acetic acid and deionized water in the acetic acid solution is 1:1;

[0023] Specifically, in step B3, the usage ratio of pyrrole, ethanol aqueous solution, functional monomer, solution A and ammonium persulfate solution is 2-3 g:150 mL:0.3-0.6 g:50 mL:3-5 mL, and the mass ratio of ethanol to water in the ethanol aqueous solution is 1:1.

[0024] The invention also discloses a steel core aluminum stranded wire obtained by the preparation method.

[0025] The working principle and beneficial effects of the present invention are:

[0026] 1. The present invention sprays anti-corrosion coating on the surface of steel core and aluminum stranded wire to form an anti-corrosion layer, which not only has excellent corrosion resistance and weather resistance, but also maintains the original mechanical properties and electrical properties of the steel core aluminum stranded wire. The hyperbranched polymer and modified filler added to the anti-corrosion coating work synergistically to improve the anti-corrosion performance of the coating. The hyperbranched polymer also acts as a curing agent and improves the mechanical properties of the coating. The modified filler is based on MXene nanosheets, and polypyrrole and functional monomers are loaded on its surface and interlayer, which synergistically improves the anti-corrosion performance of the coating.

[0027] 2. The hyperbranched polymer added to the anticorrosive coating is prepared by reacting the epoxy group in trimethylolpropane triglycidyl ether with the carboxyl group in trimesic acid to generate a product 1 containing a terminal carboxyl group. The terminal carboxyl group in the product 1 is then reacted with the amino group in pentaerythritoltetramine and 3,4-dimethoxybenzylamine to generate an amino-terminated hyperbranched precursor. Finally, boron tribromide is used to remove the methyl group in 3,4-dimethoxybenzylamine to generate a hyperbranched polymer containing a terminal amino group and a catechol structure. Hyperbranched polymers act as curing agents in anti-corrosion coatings, using terminal amino groups to react with epoxy groups in epoxy resins to perform cross-linking and curing, thereby increasing the cross-linking density of the epoxy resin molecular chains, which is beneficial for preventing corrosive media from entering the interior of the epoxy resin matrix and improving the anti-corrosion performance of the coating; the catechol structure contained in the polymer can form phenol anions, which can interact electrostatically and coordinate with the metal, allowing the coating to adhere more tightly and firmly to the metal surface to form a protective layer, thereby achieving an anti-corrosion and corrosion-inhibiting effect on the metal matrix; in addition, the hyperbranched polymer contains a large amount of soft satin structures, which increase the flexibility of the coating and improve the mechanical properties of the coating.

[0028] 3. The modified filler added to the anti-corrosion coating, first, a trityl protecting group is introduced into histidine to generate the intermediate product 1, and the protection of the amino group is to avoid the reaction between the amino group and the phosphate group in the subsequent reaction; secondly, the amide reaction between the carboxyl group in the intermediate product 1 and the amino group in (4-(aminomethyl)phenyl)phosphonic acid is used to generate a functional monomer; finally, MXene nanosheets are used as a substrate and etched to obtain a single layer or a few layers of MXene nanosheets, and then pyrrole and functional monomers are loaded on the surface of the nanosheets to generate a modified filler; the MXene nanosheets, polypyrrole and functional monomers in the modified filler synergistically improve the corrosion resistance of the substrate, wherein the MXene nanosheets have a two-dimensional sheet structure similar to graphene, and adding it to the coating as a filler substrate can make the coating produce a water barrier effect, namely the "maze effect". The coating can effectively block the diffusion of corrosive media (such as water, oxygen, etc.) in the external environment into the interior of the matrix, thereby protecting the metal matrix from corrosion; polypyrrole is loaded on the surface of the nanosheet with pyrrole as the monomer, and the functional monomer is doped into the polypyrrole by utilizing the doping characteristics of pyrrole. After polypyrrole is introduced into the coating, it can form a passivation film on the metal surface, thereby protecting the internal metal. The introduction of the functional monomer further improves the anti-corrosion effect of the coating on the metal. This is because the imidazole heterocycle and polar functional groups (amino, hydroxyl) contained in the functional monomer can interact with the metal to form a coordination bond, chemically adsorb, and form a protective film on the metal surface, further preventing the metal matrix from contacting the corrosive medium; in addition, the effective loading of polypyrrole and functional monomers on the surface of the nanosheet also improves the dispersibility of the filler in the matrix. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example 1

[0031] 1) The modified filler is prepared by the following steps:

[0032] Step B1: Add 0.01 mol of histidine to a mixture of 20 mL of chloroform and 4 mL of acetonitrile and stir evenly, then add 0.01 mol of trimethylsilyl chloride, reflux for 2 h, then cool to 0°C, then add 0.03 mol of triethylamine and 0.025 mol of trityl chloride dissolved in 10 mL of chloroform into the reactor, continue stirring and reacting for 1 h, then add 2 mL of methanol and mix evenly, concentrate, extract, and dry to obtain intermediate 1;

[0033] Step B2: 0.02 mol of intermediate product 1 and 0.02 mol of (4-(aminomethyl)phenyl)phosphonic acid were added to a flask containing 100 mL of dichloromethane, stirred and mixed evenly, and then 0.05 g of N, N'-dicyclohexylcarbodiimide was added, and the mixture was reacted for 5 h under nitrogen. After the reaction was completed, the mixture was distilled, and the product was added to 40 mL of acetic acid solution and refluxed for 10 min to obtain a functional monomer. The mass ratio of acetic acid to deionized water in the acetic acid solution was 1:1;

[0034] Step B3: 1g of MXene nanosheets etched with HCl-LiF (prepared according to the method of patent CN115041027B) and 0.5g of 3-aminopropyltriethoxysilane were dispersed in a mixture of 10mL of deionized water and 50mL of ethanol, stirred for 5h, centrifuged, washed, and redispersed in 50mL of deionized water, recorded as solution A. 2g of pyrrole was dispersed in 150mL of ethanol aqueous solution, stirred for 30min, and 0.3g of functional monomer was added and continued to stir for 1h. Subsequently, the mixed solution was added to 50mL of solution A, and 3mL of 0.1mol / L ammonium persulfate solution was slowly added dropwise at 2°C. The reaction was continued with stirring for 10h. After the reaction was completed, the modified filler was obtained by centrifugation, washing, and drying. The mass ratio of ethanol to water in the ethanol aqueous solution was 1:1.

[0035] 2) Anticorrosive coating, prepared by the following steps:

[0036] Step A1: 0.03 mol of trimesic acid, 0.01 mol of trimethylolpropane triglycidyl ether and 0.015 mol of tetrabutylammonium bromide were added into a reactor containing 200 mL of N,N-dimethylformamide, and after being mixed evenly, nitrogen was introduced into the system, and the system was heated to 90° C. for reaction for 4 h. After the reaction was completed, the system was rotary evaporated, washed and dried to obtain product 1;

[0037] Step A2: 0.01 mol of a hyperbranched precursor, 0.08 mol of pentaerythritol, and 0.03 mol of 3,4-dimethoxybenzylamine were added to a flask containing 200 mL of dichloromethane, and stirred for 30 min. Then, 0.08 g of N,N-dicyclohexylcarbodiimide was added, and the mixture was heated to 170° C. and refluxed under condensation for 5 h under nitrogen. After the reaction was completed, the mixture was distilled to obtain an amino-terminated hyperbranched precursor;

[0038] Step A3: 2 g of the amino-terminated hyperbranched precursor and 200 mL of dichloromethane were added to a flask, stirred evenly, and 4 mL of a dichloromethane solution of boron tribromide was added dropwise at 0°C, stirred and reacted for 6 h. After the reaction was completed, the hyperbranched polymer was obtained by suction filtration, washing, and drying. The mass concentration of the dichloromethane solution of boron tribromide was 0.15 g / mL.

[0039] Step A4: weigh the raw materials according to mass percentage, add 6% of hyperbranched polymer, 0.3% of defoamer BYK-A530, 0.1% of dispersant BYK190, 10% of modified filler, and the balance of epoxy resin E51 into the reactor, stir and mix for 30 minutes, and the anti-corrosion coating is obtained.

[0040] Example 2

[0041] 1) The modified filler is prepared by the following steps:

[0042] Step B1: Add 0.01 mol of histidine to a mixture of 17 mL of chloroform and 3.5 mL of acetonitrile and stir evenly, then add 0.01 mol of trimethylsilyl chloride, reflux for 2 h, then cool to 0°C, then add 0.025 mol of triethylamine and 0.019 mol of trityl chloride dissolved in 10 mL of chloroform into the reactor, continue stirring and reacting for 1 h, then add 2 mL of methanol and mix evenly, concentrate, extract, and dry to obtain intermediate 1;

[0043] Step B2: 0.015 mol of intermediate product 1 and 0.015 mol of (4-(aminomethyl)phenyl)phosphonic acid were added to a flask containing 100 mL of dichloromethane, stirred and mixed evenly, and then 0.1 g of N, N'-dicyclohexylcarbodiimide was added, and the mixture was reacted for 6 h under nitrogen. After the reaction was completed, the mixture was distilled, and the product was added to 40 mL of acetic acid solution and refluxed for 10 min to obtain a functional monomer. The mass ratio of acetic acid to deionized water in the acetic acid solution was 1:1;

[0044] Step B3: 1g of MXene nanosheets etched with HCl-LiF (prepared according to the method of patent CN115041027B) and 1g of 3-aminopropyltriethoxysilane were dispersed in a mixture of 10mL of deionized water and 50mL of ethanol, stirred for 7h, centrifuged, washed, and redispersed in 50mL of deionized water, recorded as solution A. 2.5g of pyrrole was dispersed in 150mL of ethanol aqueous solution, stirred for 30min, and 0.45g of functional monomer was added and continued to stir for 1h. Subsequently, the mixed solution was added to 50mL of solution A, and 4mL of 0.1mol / L ammonium persulfate solution was slowly added dropwise at 4°C. The reaction was continued with stirring for 11h. After the reaction was completed, the modified filler was obtained by centrifugation, washing, and drying. The mass ratio of ethanol to water in the ethanol aqueous solution was 1:1.

[0045] 2) Anticorrosive coating, prepared by the following steps:

[0046] Step A1: 0.06 mol of trimesic acid, 0.01 mol of trimethylolpropane triglycidyl ether and 0.03 mol of tetrabutylammonium bromide were added into a reactor containing 200 mL of N,N-dimethylformamide, and after being mixed evenly, nitrogen was introduced into the system, and the system was heated to 90° C. for reaction for 5 h. After the reaction was completed, the system was rotary evaporated, washed and dried to obtain product 1;

[0047] Step A2: 0.01 mol of product 1, 0.1 mol of pentaerythritol, and 0.04 mol of 3,4-dimethoxybenzylamine were added to a flask containing 200 mL of dichloromethane, and stirred for 30 min. Then, 0.02 g of N,N-dicyclohexylcarbodiimide was added, and the mixture was heated to 180° C. and refluxed under nitrogen for 6 h. After the reaction was completed, the mixture was distilled to obtain an amino-terminated hyperbranched precursor;

[0048] Step A3: 2.5 g of the amino-terminated hyperbranched precursor and 200 mL of dichloromethane were added to a flask, stirred evenly, and 6 mL of a dichloromethane solution of boron tribromide was added dropwise at 2° C. The mixture was stirred for 8 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a hyperbranched polymer. The mass concentration of the dichloromethane solution of boron tribromide was 0.25 g / mL.

[0049] Step A4: weigh the raw materials according to mass percentage, add 10% of hyperbranched polymer, 0.5% of defoamer BYK-A530, 0.3% of dispersant BYK190, 12% of modified filler, and the balance of epoxy resin E51 into the reactor, stir and mix for 30 minutes, and the anti-corrosion coating is obtained.

[0050] Example 3

[0051] 1) The modified filler is prepared by the following steps:

[0052] Step B1: Add 0.01 mol of histidine to a mixture of 20 mL of chloroform and 4 mL of acetonitrile and stir evenly, then add 0.01 mol of trimethylsilyl chloride, reflux for 2 h, then cool to 0°C, then add 0.03 mol of triethylamine and 0.025 mol of trityl chloride dissolved in 10 mL of chloroform into the reactor, continue stirring and reacting for 1 h, then add 2 mL of methanol and mix evenly, concentrate, extract, and dry to obtain intermediate 1;

[0053] Step B2: 0.02 mol of the intermediate product 1 and 0.02 mol of (4-(aminomethyl)phenyl)phosphonic acid were added to a flask containing 100 mL of dichloromethane, stirred and mixed evenly, and then 0.15 g of N, N'-dicyclohexylcarbodiimide was added, and the mixture was reacted for 7 h under nitrogen. After the reaction was completed, the mixture was distilled, and the product was added to 40 mL of acetic acid solution and refluxed for 10 min to obtain a functional monomer. The mass ratio of acetic acid to deionized water in the acetic acid solution was 1:1;

[0054] Step B3: 1g of MXene nanosheets etched with HCl-LiF (prepared according to the method of patent CN115041027B) and 2g of 3-aminopropyltriethoxysilane were dispersed in a mixture of 10mL of deionized water and 50mL of ethanol, stirred for 10h, centrifuged, washed, and redispersed in 50mL of deionized water, recorded as solution A. 3g of pyrrole was dispersed in 150mL of ethanol aqueous solution, stirred for 30min, and 0.6g of functional monomer was added and continued to stir for 1h. Subsequently, the mixed solution was added to 50mL of solution A, and 5mL of 0.1mol / L ammonium persulfate solution was slowly added dropwise at 5°C. The reaction was continued with stirring for 12h. After the reaction was completed, the modified filler was obtained by centrifugation, washing, and drying. The mass ratio of ethanol to water in the ethanol aqueous solution was 1:1.

[0055] 2) Anticorrosive coating, prepared by the following steps:

[0056] Step A1: 0.09 mol of trimesic acid, 0.01 mol of trimethylolpropane triglycidyl ether and 0.045 mol of tetrabutylammonium bromide were added into a reactor containing 200 mL of N,N-dimethylformamide, and after being mixed evenly, nitrogen was introduced into the system, and the system was heated to 90° C. for reaction for 6 h. After the reaction was completed, the system was rotary evaporated, washed and dried to obtain product 1;

[0057] Step A2: 0.01 mol of product 1, 0.12 mol of pentaerythritol, and 0.05 mol of 3,4-dimethoxybenzylamine were added to a flask containing 200 mL of dichloromethane, stirred for 30 min, and then 0.2 g of N,N-dicyclohexylcarbodiimide was added, and heated to 200° C. under nitrogen conditions, condensed and refluxed for 7 h. After the reaction was completed, distillation was performed to obtain an amino-terminated hyperbranched precursor;

[0058] Step A3: 3 g of amino-terminated hyperbranched precursor and 200 mL of dichloromethane were added to a flask, stirred evenly, and 8 mL of dichloromethane solution of boron tribromide was added dropwise at 5° C. The mixture was stirred for 10 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a hyperbranched polymer. The mass concentration of the dichloromethane solution of boron tribromide was 0.35 g / mL.

[0059] Step A4: weigh the raw materials according to mass percentage, add 12% of hyperbranched polymer, 0.7% of defoamer BYK-A530, 0.5% of dispersant BYK190, 15% of modified filler, and the balance of epoxy resin E51 into the reactor, stir and mix for 30 minutes, and the anti-corrosion coating is obtained.

[0060] Example 4

[0061] A method for preparing a steel core aluminum stranded wire comprises the following steps:

[0062] Step S1: After the steel core is degreased, washed, dried, and sandblasted to remove rust, the anticorrosive coating prepared in Example 1 with a thickness of 5.0 μm is sprayed on the surface of the steel core, and the steel core is allowed to stand and dry to obtain a pretreated steel core;

[0063] Step S2: The aluminum wire is wound on the pretreated steel core in two layers, with the inner layer having 12 strands and the outer layer having 14 strands, and then immersed in a 10wt% boiling sodium hydroxide solution for 3 min, washed, dried, and sandblasted, and then sprayed with the anti-corrosion coating prepared in Example 1 with a thickness of 10 µm, and then washed and dried to obtain a steel core aluminum stranded wire.

[0064] Example 5

[0065] A method for preparing a steel core aluminum stranded wire comprises the following steps:

[0066] Step S1: After the steel core is degreased, washed, dried, and sandblasted to remove rust, the anticorrosive coating prepared in Example 2 with a thickness of 6.0 μm is sprayed on the surface of the steel core, and after standing and drying, a pretreated steel core is obtained;

[0067] Step S2: The aluminum wire is wound on the pretreated steel core in two layers, with the inner layer having 12 strands and the outer layer having 14 strands, and then immersed in a 10wt% boiling sodium hydroxide solution for 5 min, washed, dried, and sandblasted, and then sprayed with the anti-corrosion coating prepared in Example 2 with a thickness of 15 µm, and then washed and dried to obtain the steel core aluminum stranded wire.

[0068] Example 6

[0069] A method for preparing a steel core aluminum stranded wire comprises the following steps:

[0070] Step S1: After the steel core is degreased, washed, dried, and sandblasted to remove rust, the anticorrosive coating prepared in Example 3 with a thickness of 8.0 μm is sprayed on the surface of the steel core, and the steel core is allowed to stand and dry to obtain a pretreated steel core;

[0071] Step S2: The aluminum wire is wound on the pretreated steel core in two layers, with the inner layer having 12 strands and the outer layer having 14 strands, and then immersed in a 10wt% boiling sodium hydroxide solution for 7 minutes, washed, dried, and sandblasted, and then sprayed with the anti-corrosion coating prepared in Example 3 with a thickness of 20µm, and then washed and dried to obtain the steel core aluminum stranded wire.

[0072] Comparative Example 1

[0073] This comparative example is a steel core aluminum stranded wire, which differs from Example 6 in that the sprayed coating is different. Specifically, the coating differs from the anti-corrosion coating prepared in Example 3 in that an equal amount of ethylenediamine is used instead of the hyperbranched polymer, and the rest are the same.

[0074] Comparative Example 2

[0075] This comparative example is a steel core aluminum stranded wire, which differs from Example 6 in that the sprayed coating is different. Specifically, the coating differs from the anti-corrosion coating prepared in Example 3 in that an equal amount of nano calcium carbonate is used to replace the modified filler, and the rest is the same.

[0076] Performance Test:

[0077] The steel core aluminum stranded wires prepared in Examples 4-6 and Comparative Examples 1-2 were placed in simulated environments with climatic conditions such as coastal industrial areas (3wt% NaCl+3wt% NaHSO3), industrial areas (3wt% NaHSO3), coastal areas (3wt% NaCl) and rural areas (H2O) for immersion corrosion tests. The immersion time was 72 hours, and the changes in the surface coating were observed. The test results are shown in the following table:

[0078]

[0079] It can be seen from the above table that the steel core aluminum stranded wire prepared by the present invention can adapt to the climatic conditions of coastal industrial areas, industrial areas, coastal areas and rural areas, and has excellent corrosion resistance.

[0080] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a steel core aluminum stranded wire, characterized in that: The following steps are involved: Step S1: After the steel core is degreased, washed, dried, and sandblasted to remove rust, an anti-corrosion coating with a thickness of 5.0-8.0 µm is sprayed on the surface of the steel core, and the steel core is allowed to stand and dry to obtain a pretreated steel core; Step S2: Wrap the aluminum wire in two layers on the pretreated steel core, with the inner layer being 12 strands and the outer layer being 14 strands, and then soak the wire in a 10wt% boiling sodium hydroxide solution for 3-7 minutes, wash, dry, and sandblast, and then spray an anti-corrosion coating with a thickness of 10-20µm, and then wash and dry to obtain a steel core aluminum stranded wire; The anticorrosive coating is prepared by the following steps: Step A1: add trimesic acid, trimethylolpropane triglycidyl ether and tetrabutylammonium bromide into a reactor containing N,N-dimethylformamide, mix well, introduce nitrogen into the system, heat to 90°C for reaction for 4-6h, and after the reaction is completed, rotary evaporate, wash and dry to obtain product 1; Step A2: Add product 1, pentaerythritol tetramine and 3,4-dimethoxybenzylamine into a flask containing dichloromethane, stir for 30 minutes, then add N,N-dicyclohexylcarbodiimide, and heat to 170-200° C. under nitrogen, condense and reflux for 5-7 hours. After the reaction is completed, distill to obtain an amino-terminated hyperbranched precursor; Step A3: Add the amino-terminated hyperbranched precursor and dichloromethane into a flask, stir evenly, dropwise add a dichloromethane solution of boron tribromide at 0-5°C, stir and react for 6-10 hours, and after the reaction is completed, filter, wash and dry to obtain a hyperbranched polymer; Step A4: weigh the raw materials according to mass percentage, add 6%-12% of hyperbranched polymer, 0.3%-0.7% of defoamer, 0.1%-0.5% of dispersant and 10%-15% of modified filler into 71.8%-83.6% of epoxy resin, and stir and mix for 30 minutes to obtain an anti-corrosion coating; The modified filler is prepared by the following steps: Step B1: add histidine to a mixture of chloroform and acetonitrile and stir evenly, then add trimethylsilyl chloride, reflux for 2 hours, then cool to 0°C, then add triethylamine and trityl chloride dissolved in chloroform into the reactor, continue stirring and reacting for 1 hour, then add methanol and mix evenly, concentrate, extract and dry to obtain intermediate 1; Step B2: Add the intermediate product 1 and (4-(aminomethyl)phenyl)phosphonic acid into a flask containing dichloromethane, stir and mix evenly, then add N,N'-dicyclohexylcarbodiimide, and heat to 170-200°C under nitrogen, condense and reflux for 3-5h. After the reaction is completed, distill, and then add the product into 40mL acetic acid solution and reflux for 10min to obtain a functional monomer; Step B3: Disperse 1 g of MXene nanosheets etched with HCl-LiF and 0.5-2 g of 3-aminopropyltriethoxysilane in a mixture of 10 mL of deionized water and 50 mL of ethanol, stir for 5-10 h, centrifuge, wash, and redisperse in 50 mL of deionized water, recorded as solution A. Disperse pyrrole in an ethanol-water solution, stir for 30 min, add the functional monomer and continue stirring for 1 h. Subsequently, add the mixed solution to solution A, and slowly add 0.1 mol / L ammonium persulfate solution at 2-5 ° C. Continue stirring for 10-12 h. After the reaction is completed, centrifuge, wash, and dry to obtain a modified filler.

2. The method for preparing a steel core aluminum stranded wire according to claim 1, characterized in that: In step A1, the usage ratio of trimesic acid, trimethylolpropane triglycidyl ether, tetrabutylammonium bromide and N,N-dimethylformamide is 0.03-0.09 mol: 0.01 mol: 0.015-0.045 mol: 200 mL.

3. The method for preparing a steel core aluminum stranded wire according to claim 1, characterized in that: In step A2, the usage ratio of product 1, pentaerythritol, 3,4-dimethoxybenzylamine, dichloromethane and N,N-dicyclohexylcarbodiimide is 0.01 mol: 0.08-0.12 mol: 0.03-0.05 mol: 200 mL: 0.08-0.2 g.

4. The method for preparing a steel core aluminum stranded wire according to claim 1, characterized in that: In step A3, the usage ratio of the terminal amino hyperbranched precursor, dichloromethane and dichloromethane solution of boron tribromide is 2-3 g: 200 mL: 4-8 mL, and the mass concentration of the dichloromethane solution of boron tribromide is 0.15-0.35 g / mL.

5. The method for preparing a steel core aluminum stranded wire according to claim 1, characterized in that: In step B1, the usage ratio of histidine, chloroform, acetonitrile, trimethylsilyl chloride, chloroform, triethylamine, trityl chloride and methanol is 0.01 mol: 15-20 mL: 3-4 mL: 0.01 mol: 10 mL: 0.02-0.03 mol: 0.01-0.025 mol: 2 mL.

6. The method for preparing a steel core aluminum stranded wire according to claim 1, characterized in that: In step B2, the usage ratio of intermediate product 1, (4-(aminomethyl)phenyl)phosphonic acid, dichloromethane and N,N'-dicyclohexylcarbodiimide is 0.01-0.02 mol: 0.01-0.02 mol: 100 mL: 0.05-0.15 g, and the mass ratio of acetic acid and deionized water in the acetic acid solution is 1:

1.

7. The method for preparing a steel core aluminum stranded wire according to claim 1, characterized in that: In step B3, the usage ratio of pyrrole, ethanol aqueous solution, functional monomer, solution A and ammonium persulfate solution is 2-3 g:150 mL:0.3-0.6 g:50 mL:3-5 mL, and the mass ratio of ethanol to water in the ethanol aqueous solution is 1:

1.

8. A steel core aluminum stranded wire, characterized in that: The steel core aluminum stranded wire is prepared according to the method according to any one of claims 1-7.

Citation Information

Patent Citations

  • A dual-regulated two-dimensional MXene composite film and its preparation method

    CN115041027B

  • Preparation method of metal corrosion inhibition and corrosion prevention coating

    CN117025063A

  • Corrosion-resistant steel-cored aluminum strand and preparation method thereof

    CN117410020A